2022
DOI: 10.3390/horticulturae8100940
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potassium Application on Lilium davidii var. unicolor Growth, Polysaccharide Accumulation, and Metabolism

Abstract: Lilium davidii var. unicolor is an important variety of lily with high economic, ornamental, edible, and medicinal values. Up to now, the research on polysaccharide as the main active substance is not vast, especially the effect of potassium on lily polysaccharide. Here, we investigated the effects of potassium fertilizer application on the growth and development, polysaccharide accumulation in the bulb, and differential metabolites in L. davidii var. unicolor. It was treated with fixed amounts of nitrogen (N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…As for other nutrients, these results suggest that fertigation with K should be started early in the season. This initial high K accumulation may be associated with the synthesis and accumulation of polysaccharides in the bulbs, as reported by Sha et al [39] in L. davidii. At the end of the season, 44.3% of the total K measured in the plant came from the bulb, while the remaining 55.4% was absorbed from the growing medium (Table 1), and flowering was the developmental phase with the highest accumulation, as 89.3% of the total K was absorbed in this phase.…”
Section: Potassiumsupporting
confidence: 68%
“…As for other nutrients, these results suggest that fertigation with K should be started early in the season. This initial high K accumulation may be associated with the synthesis and accumulation of polysaccharides in the bulbs, as reported by Sha et al [39] in L. davidii. At the end of the season, 44.3% of the total K measured in the plant came from the bulb, while the remaining 55.4% was absorbed from the growing medium (Table 1), and flowering was the developmental phase with the highest accumulation, as 89.3% of the total K was absorbed in this phase.…”
Section: Potassiumsupporting
confidence: 68%
“…epidermidis in the presence of commercial polysaccharides dextran (α1,6-glucan) and laminarin (β1,3-glucan) and PIS that were extracted from S. epidermidis by using the ethanol precipitation method. Figure a shows that the presence of all three polysaccharides at a concentration of 4.5 μg/mL can significantly reduce the antibacterial activity of G3 and increase the MIC by more than 2 times. Compared with dextran and laminarin, PIS had the most obvious effects and could increase the MIC by 3 times.…”
Section: Resultsmentioning
confidence: 99%
“…The surface hydrophobicity of bacteria was expressed as the percentage reduction of the A 550 readings of the aqueous phase after mixing with the organic phase. In addition, the hydrophobicity of bacteria, which was incubated with G3 at a concentration of 4 μM for different time intervals (1,5,10,20,30,40,50, and 60 min), was also measured with the above method.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…During the cultivation process of horticultural plants, fertilizers are used to ensure the plants' normal growth and improve their quality. Potassium fertilizer has been found to affect the accumulation of nutrients in plants [10]. Several studies have shown that the application of potassium fertilizer can increase the content of polysaccharides and other macromolecules in Lanzhou lily bulbs.…”
Section: Introductionmentioning
confidence: 99%